Olive Oil - Constituents, Quality, Health Properties and Bioconversions 2012
DOI: 10.5772/28512
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Composition: Volatile Compounds

Abstract: The health-promoting effects attributed to olive oil, and the development of the olive oil industry have intensified the quest for new information, stimulating wide areas of research. This book is a source of recently accumulated information. It covers a broad range of topics from chemistry, technology, and quality assessment, to bioavailability and function of important molecules, recovery of bioactive compounds, preparation of olive oil-based functional products, and identification of novel pharmacological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 137 publications
0
15
0
Order By: Relevance
“…The compounds in the vapor phase were extracted using a solid phase microextraction fiber with DVB/CAR/PDMS (divinylbenzene, carboxen, and polydimethylsiloxane). After 30 min of extraction (Silva et al 2012), the fiber was injected into a gas chromatograph coupled with mass spectrometer (GC-MS Shimadzu QP2010 Ultra) equipped with an autosampler (CombiPAL AOC -5000) and an Equity-5 column (5% phenyl -95% dimethylpolysiloxane, 30 m × 0.25 mm × 0.25 mm). The injection was made in the splitless mode using helium as the carrier gas at a rate of 1.0 mL•min -1 .…”
Section: Volatile Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The compounds in the vapor phase were extracted using a solid phase microextraction fiber with DVB/CAR/PDMS (divinylbenzene, carboxen, and polydimethylsiloxane). After 30 min of extraction (Silva et al 2012), the fiber was injected into a gas chromatograph coupled with mass spectrometer (GC-MS Shimadzu QP2010 Ultra) equipped with an autosampler (CombiPAL AOC -5000) and an Equity-5 column (5% phenyl -95% dimethylpolysiloxane, 30 m × 0.25 mm × 0.25 mm). The injection was made in the splitless mode using helium as the carrier gas at a rate of 1.0 mL•min -1 .…”
Section: Volatile Profilementioning
confidence: 99%
“…Furthermore, Prenzler et al (2002), Krichene et al (2010) and Kiralan et al (2012) showed that E-2-hexenal is the dominant compound in some Australian, Tunisian and Turkish VOOs, besides the minor contribution of C5 compounds to the volatile profiles. E-2-hexenal is derived from the enzymatic conversion of fatty acids and can be used as a marker of quality and freshness (Tanouti et al 2012), and it is inversely related to the degree of oxidation of virgin olive oil (Silva et al 2012).…”
Section: Volatile Profilementioning
confidence: 99%
“…Some of these compounds, specially disulfide and trisulfide derivates are known to have antioxidant properties [29]. Regarding the olive oil ingredients, four main volatiles were identified (2,4-heptadienal, 1,2-dimethyl-benzene, benzeneacetaldehyde and 1-octanol) [41].…”
Section: Resultsmentioning
confidence: 99%
“…The AAUP-NARC team has identified three general categories or factors that broadly can have an influence on olive oil quality: pre-harvest conditions of olive tree and fruits; processing and extraction of olive oil from its fruits; and post-extraction handling and storage (Zaid et al, 2013;Houshia et al, 2014a, b, c, d). The pre-harvest conditions, harvest date and harvest year influence the biometrics of olives (Giuffrè, 2017) and the physicochemical composition properties of olive oil, such as phenols (Agiomyrgianaki et al, 2012), sterols (Giuffrè and Louadj, 2013), fatty alcohols (Giuffrè, 2014a), wax esters (Giuffrè, 2014b), tryglycerides (Giuffrè, 2014c) fatty acids (Krichène et al, 2010) and volatiles (Silva et al, 2012;Cherfaoui et al, 2018). Additionally, both pre-and post-harvest factors can have an impact on quality of olive fruit and on oil composition (Mele et al, 2018).…”
Section: Introductionmentioning
confidence: 99%